Factorial invariance of the abridged version of the Explicit Discrimination Scale among adults living in southern Brazil - Fabiula Renilda Bernardo; João Luiz Bastos; Michael Eduardo Reichenheim (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective The Explicit Discrimination Scale (EDS) was developed to assess experiences with discrimination in Brazilian epidemiologic surveys. Though previous analyses have demonstrated that the EDS has good configural, metric, and scalar properties, its invariance has not yet been investigated. In this study, we examined the factorial invariance of two abridged versions of the EDS, according to skin color/ethnicity, sex, socioeconomic status, and their intersections. Methods: Data from the EpiFloripa Adult Study were used, which include a representative sample of adults residing in a state capital of southern Brazil (n=1,187). Over half of the respondents were women, and around 90% identified as white; the mean age of the participants was 39 years. Two abridged versions of the EDS were analyzed, with seven and eight items, using Multigroup Confirmatory Analysis and the Alignment method. Results: The two versions of the scale may be used to provide estimates of discrimination that are comparable across skin color/ethnicity, sex, socioeconomic status, and their intersections. In the seven-item version of the scale, only one parameter lacked invariance (i.e., threshold of item i13 - called by names you do not like), specifically among black respondents with less than 12 years of formal education. Conclusion: The EDS may provide researchers with valid, reliable, and comparable estimates of discrimination between different segments of the population, including those at the intersections of skin color/ethnicity, sex, and socioeconomic status. However, future research is needed to determine whether the patterns we identified here are consistent in other population domains.